An experimental and analytical study on the out-of-plane behavior of URM prisms strengthened with SFRC overlays. (October 2021) - Dehghan, S.M.; Karamian, M.R.; Najafgholipour, M.A.
Abstract: The observed failures in recent earthquakes have demonstrated the out-of-plane vulnerability of unreinforced masonry walls. An extensive experimental investigation was conducted on the application of hooked steel fibers as reinforcement in concrete overlays for the out-of-plane strengthening of solid clay brick masonry prisms. The variables included the thickness of the overlay (20, 30, and 40 mm), the thickness of the masonry prisms (single-leaf and double-leaf), the strengthening sides (one side and both sides), the overlay loading condition, and the steel fiber content. The test results were compared qualitatively (observations and failure modes) and quantitatively (load–deflection diagrams, ultimate loads, and flexural strengths). Moreover, an analytical model was utilized to evaluate the load-bearing capacity of the experimental results. The SFRC overlays considerably improved the behavior of the specimens in terms of load-bearing capacity and flexural stiffness although the thickness of the SFRC overlays was more effective than the volume fraction of the steel fibers in the overlays.